PERAN GURU DALAM MENINGKATKAN MORAL ANAK USIA DINI TKIT YAA BUNAYYA 1 HIDAYATULLAH KARIMUN TAHUN 2023/2024 - Nurul Hidayah (UNISAN JURNAL, 2024)
The purpose of this research is to determine: 1) How teachers act as guides in enhancing the moral development of early childhood children at TK IT Yaa Bunayya 1 Hidayatullah Karimun; and 2) How teachers act as educators in improving the moral development of early childhood children at TK IT Yaa Bunayya 1 Hidayatullah Karimun. This research utilizes qualitative methodology, specifically a case study approach. Data collection techniques involve interviews and documentation. Data analysis follows the concept proposed by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The research findings indicate that: 1) In line with the preconventional morality of children who are disobedient to rules, they are subjected to punishment, such as using a song as a reminder when a child hits their peer without reason; 2) Children are inherently good, so teaching practices at school are planned, implemented, and evaluated, then documented in lesson plans. Keywords: Teacher’s Role, Moral Development Of Early Childhood